2014
DOI: 10.1002/2327-6924.12124
|View full text |Cite
|
Sign up to set email alerts
|

Supporting cardiovascular risk reduction in overweight and obese hypertensive patients through DASH diet and lifestyle education by primary care nurse practitioners

Abstract: Purpose To describe an intervention among overweight and obese hypertensive patients, encouraging Dietary Approaches to Stop Hypertension (DASH) diet and lifestyle changes, designed and led by a primary care nurse practitioner (NP). Data sources A pre‐ and postintervention quasi‐experimental time‐series design was implemented over 2 months. Intervention included three group classes and two individual counseling telephone calls. Forty‐five hypertensive patients enrolled, with a mean age of 55 years and mean ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…A combination of educational training on lifestyle modification and a peer group intervention also had benefits on cardiovascular risk factors over a 1‐year period among adults at risk of cardiovascular disease (Gomez‐Pardo et al., ). Similar results have been reported by studies which implemented nurse‐led education programmes based on lifestyle group counselling in primary healthcare settings (Gilis‐Januszewska et al., ; Jarl, Tolentino, James, Clark, & Ryan, ; Laatikainen et al., ).…”
Section: Introductionsupporting
confidence: 84%
“…A combination of educational training on lifestyle modification and a peer group intervention also had benefits on cardiovascular risk factors over a 1‐year period among adults at risk of cardiovascular disease (Gomez‐Pardo et al., ). Similar results have been reported by studies which implemented nurse‐led education programmes based on lifestyle group counselling in primary healthcare settings (Gilis‐Januszewska et al., ; Jarl, Tolentino, James, Clark, & Ryan, ; Laatikainen et al., ).…”
Section: Introductionsupporting
confidence: 84%
“…) and smoking cessation (Harbman , Jarl et al . ). It should be noted that our study evaluated the long‐term effects of NP‐led interventions, and this could have contributed to the lack of differences in some variables detected in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Studies that reported a positive impact were mainly short term (Harbman , Jarl et al . , Richardson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples included diabetes management (Chang, Davis et al 2007, McCarrier, Ralston et al 2009, Conlon 2010, Stone, MacPherson et al 2010, Choi and Rush 2012, Jessee and Rutledge 2012, Murfet, Allen et al 2013 or encouraging healthy lifestyle changes (Speck, Hines-Martin et al 2007, Goessens, Visseren et al 2008, Perman 2008, Marion, Finnegan et al 2009, Whittemore, Melkus et al 2009, Whittemore, Melkus et al 2010, Courtney, Conard et al 2011, Stines, Perman et al 2011, Ter Bogt, Milder et al 2011, Vermunt, Milder et al 2011, Barte, ter Bogt et al 2012, Vermunt, Milder et al 2012, Jarl, Tolentino et al 2014. Although these programs did not ignore factors influencing patients' psychosocial health, it was clear that the focus was around treating or preventing exacerbation of existing conditions rather than addressing determinants of health.…”
Section: Nurse Practitioners In Primary Health Care Settingsmentioning
confidence: 99%
“…In addition to the care populations identified, such as diabetes (Chang, Davis et al 2007, McCarrier, Ralston et al 2009, Conlon 2010, Stone, MacPherson et al 2010, Vermunt, Milder et al 2011, Choi and Rush 2012, Jessee and Rutledge 2012, Vermunt, Milder et al 2012, Murfet, Allen et al 2013 or the presence lifestyle risk factors for chronic disease (Speck, Hines-Martin et al 2007, Goessens, Visseren et al 2008, Stines, Perman et al 2011, Ter Bogt, Milder et al 2011, Barte, ter Bogt et al 2012, Allen, Dennison Himmelfarb et al 2014, Jarl, Tolentino et al 2014, nurse practitioners worked with populations who were considered vulnerable. This included ethnic groups identified as being at risk (Marion, Finnegan et al 2009, Choi and Rush 2012, Barrett , Salem et al 2015, Murphy, Coke et al 2015, individuals and groups from rural areas (Wright, Purdy et al 2007, Jessee and Rutledge 2012, Murfet, Allen et al 2013, Barrett , Salem et al 2015, Kozlowski, Lusk et al 2015, Tokuda, Lorenzo et al 2016, Tyler and Horner 2016, areas of socio-economic disadvantage (Speck, Hines-Martin et al 2007, Marion, Finnegan et al 2009, Lynam, Loock et al 2010, Stines, Perman et al 2011, Wong, Lynam et al 2012, Walker, Marshall et al 2013, Ri...…”
Section: Who Do Nurse Practitioners Work With?mentioning
confidence: 99%